ANALYZE MACHINE MAINTENANCE COST WITH CORRECTIVE METHOD AND PREVENTIVE METHOD TO INCREASE PRODUCTION RESULT - Purnama, Chamdan (Fakultas Pendidikan Ekonomi dan Bisnis, 2019)
The object of research is the engine maintenance system that is on the CV. Fajar Offset. The production process is often disrupted by the high amount of damage, which results in maintenance costs. Machines that often experience damage affect the printed product to be produced. The amount of downtime will affect the profits that will have an effect on the swollen maintenance costs of the budget that has been prepared. The purpose of this study is to analyze the cost of machine maintenance with corrective method and preventive method against increase production result. The results showed that machine maintenance was done by corrective method and preventive method proven to have an effect on increase production result.